Loop Suture Technique for Optional Adjustment in Strabismus Surgery - Parikh, Rishi K. (Medknow Publications & Media Pvt Ltd, 2013)
PURPOSE: To describe a loop suture technique that allows intraoperative conjunctival closure and later optional suture adjustment in strabismus surgery in uncooperative patients. MATERIALS AND METHODS: This retrospective case series comprised 25 patients. After a recessed or resected horizontal muscle was secured to the sclera with a primary suture suspended back 2 mm, a second loop suture was passed through the body of the muscle and under the primary suture knot. The loop suture could be removed later while the patient was awake, or it could be tied to advance the muscle. Success was defined as a residual deviation of 10 prism diopters (PD) or less at 2 months postoperatively. RESULTS: In the study cohort, 20 patients had successful alignment at 2 months (80%). Six patients (24%) underwent postoperative suture tightening by the loop technique, and each muscle affected the alignment an average of 7.7 PD (±3.8 PD). No patients underwent a reoperation within the first 2 months. One patient had a pyogenic granuloma (4%). CONCLUSIONS: The loop suture technique permits optional postoperative tightening of muscles and avoids sedation in children or uncooperative patients not requiring adjustment.